1998
DOI: 10.1046/j.1365-2648.1998.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Preconditions for and consequences of self‐determination: the psychiatric patient’s point of view

Abstract: In the context of an interview study concerned with self-determination in psychiatric patients, this paper describes the preconditions for and consequences of self-determination from the point of view of psychiatric patients themselves. The data were collected in semi-structured interviews with long-term psychiatric patients (n = 72) and analysed using the method of content analysis. Responses on the preconditions for self-determination were grouped into three categories: firstly, there were those who said tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…Self‐determination is an important concept within health care as well as an important right for the patient regardless of age, sex, cultural or social background (Välimäki & Leino‐Kilpi 1998). The concept originates in the liberal idea of free and independent individuals having the ability to take rational decisions (Mill 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Self‐determination is an important concept within health care as well as an important right for the patient regardless of age, sex, cultural or social background (Välimäki & Leino‐Kilpi 1998). The concept originates in the liberal idea of free and independent individuals having the ability to take rational decisions (Mill 1974).…”
Section: Introductionmentioning
confidence: 99%
“…40 These are, for example, the nature of patients' disease, their motivation, their current health status and information they have received. 46 Nursing staff therefore have an important role in supporting the realization of patient self-determination in health care settings. 40,[44][45][46][47] …”
Section: The Concept Of Self-determinationmentioning
confidence: 99%
“…46 Nursing staff therefore have an important role in supporting the realization of patient self-determination in health care settings. 40,[44][45][46][47] …”
Section: The Concept Of Self-determinationmentioning
confidence: 99%
“…Olofsson and Jacobsson (2001) found that patients' experiences of the involuntary process produced three themes: not being involved in one's care, receiving care that is perceived as meaningless and not good, and being an inferior kind of human being. Involvement in care is related to greater patient satisfaction and improved outcomes (Hamann et al, 2005;Lowry, 1998;Valimaki & Leino-Kilpi, 1998). Thus, efforts to involve patients in their care are desirable even when their autonomy is limited.…”
Section: Autonomymentioning
confidence: 99%